A Meal High in Saturated Fat Evokes Postprandial Dyslipemia, Hyperinsulinemia, and Altered Lipoprotein Expression in Obese Children With and Without Nonalcoholic Fatty Liver Disease. Issue 4 (5th December 2012) - Mager, Diana R.; Mazurak, Vera; Rodriguez‐Dimitrescu, Carla; Vine, Donna; Jetha, Mary; Ball, Geoff; Yap, Jason
Abstract : Background : Hyperinsulinemia and altered lipid and lipoprotein metabolism induced by fast‐food diets may contribute to nonalcoholic fatty liver disease (NAFLD). We hypothesized that a high saturated fat (SFA) meal would evoke prolonged postprandial lipemia and hyperinsulinemia, increased inflammation, and altered lipoprotein expression in obese children with NAFLD when compared with healthy children. Methods : We prospectively studied 31 children (NAFLD, 13.1 ± 2.6 years, n = 11; age‐matched obese, 14.3 ± 1.7 years, n = 9; lean, 13.6 ± 2.6 years, n = 11) following consumption of a high SFA (18.8%) meal. Prior to and at 1, 3, and 6 hours after meal consumption, blood was collected for analysis of alanine aminotransferase (ALT); aspartate aminotransferase (AST); γ‐glutamyltransferase; leptin; C‐reactive protein; (fasting) insulin; glucose; triglycerides (TGs); total, high‐density lipoprotein, and low‐density lipoprotein cholesterol; adiponectin; nonesterified fatty acids (NEFAs); inflammatory markers (TNF‐α, IL‐6, IL‐10); apolipoproteins‐B48, B100, and CIII; and fatty acid (FA) composition of TG fractions. Results : Children with NAFLD had significantly higher fasting levels of ALT (87 ± 54 U/L), AST (52 ± 33.5 U/L), and apolipoprotein‐CIII (20.6 ± 11.3 mg/dL) with postprandial hyperinsulinemia (iAUC insulin: 225 ± 207 [NAFLD] vs 113 ± 73 [obese] vs 47 ± 19.9 [lean] mU/L‐h; P < .001); suppression of NEFA (iAUC‐NEFA: 1.7 ± 0.9 [NAFLD] vs 0.6 ± 0.3 [obese] vs 1 ± 0.7 [lean] mEq/L‐h); and prolonged elevations in apolipoprotein‐B48 3–6 hours after meal consumption when compared with obese and lean controls ( P < .05). Conclusion : A meal high in saturated fat evokes postprandial dyslipemia, hyperinsulinemia, and altered lipoprotein expression in obese children with and without NAFLD.